Evaluation of shear geophones in MASW testing. Issue 2 (4th March 2019) - Khan, Zahid; Yamin, Mohammad
Abstract: Dynamic properties such as wave velocities and damping ratios are required for dynamic analyses of sites. Wave velocities in field are typically evaluated by MASW (Multichannel Analysis of Surface Waves). MASW is favoured due to its ability to resolve hidden layers and better characterisation of shallow depths. Vertical geophones that measure vertical component of motion are typically used in MASW. Shear geophones that measure the horizontal component of motion are increasingly being used in seismic surveys; however, their ability to measure Raleigh velocities in MASW testing has not been evaluated. This study presents the results of numerical simulations and experimental program that evaluates the suitability of shear geophones in MASW. The shear wave velocity profiles from vertical and horizontal components of particle motion due to Raleigh wave propagation are computed and compared. The results of this study suggest that shear geophones can be used in lieu of vertical geophones in MASW testing. Simultaneous measurements of horizontal and vertical components of particle motion can become a promising technique in future to isolate surface waves and enhance Raleigh modes using correlation techniques.